Exploring load balancing in heterogeneous networks by rate distribution. (2nd June 2010) - Haldar, Kuheli Louha; Jun, Jung-Hyun; Oliveira, Talmai; Agrawal, Dharma P.
In a heterogeneous wireless network (HWN), traffic is distributed primarily by grouping and channelling identical traffic through a particular access point. In this paper, we introduce an effective traffic load balancing scheme for maximising expected throughput in HWNs. Two scenarios are explored. First, we model multiple APs of a HWN as a cascade of independent M/M/1 queues. The expected number of packets in the system is formulated as a convex optimisation problem and solved using a Lagrange multiplier. A recursive approach is used in distributing the traffic to different APs. Then, we model multiple APs as a union of multiple M/M/1 and M/D/1 queues. Here, we minimise the time spent by each job in the system. We use a solver to obtain optimal rate distribution among the networks. Through extensive simulations, we show that distributing the traffic optimally outperforms existing traditional methods of grouping and channelling similar kind of traffic.